2021
DOI: 10.1002/prot.26155
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thePETaseconformational changes induced by poly(ethylene terephthalate) binding

Abstract: Recently, a bacterium strain of Ideonella sakaiensis was identified with the uncommon ability to degrade the poly(ethylene terephthalate) (PET). The PETase from I. sakaiensis strain 201‐F6 (IsPETase) catalyzes the hydrolysis of PET converting it to mono(2‐hydroxyethyl) terephthalic acid (MHET), bis(2‐hydroxyethyl)‐TPA (BHET), and terephthalic acid (TPA). Despite the potential of this enzyme for mitigation or elimination of environmental contaminants, one of the limitations of the use of IsPETase for PET degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 70 publications
4
50
0
Order By: Relevance
“…In the present work a PET hexamer of monohydroxyethyl terephthalate 2-HE-(MHET) 6 , was used to search for potential additional binding pockets for the ligand. The analysis of the docked poses of the PET hexamer 2-HE-(MHET) 6 shows that the terminal monomers (which interact with regions of the proteins located before and after the subsite I and IIc, respectively) display a high flexibility, while the conformation of the four central monomers (which bind the enzyme in the subsites I, IIa, IIb, and IIc) is similar to the one reported in previous studies [ 16 , 18 , 19 , 20 ] in which the tetramer 2-HE-(MHET) 4 was used as the ligand. The ligand-enzyme complex was analyzed by MD simulation ( Figure 2 A and Figure S1 ) to assess the stability of such interactions.…”
Section: Resultssupporting
confidence: 78%
“…In the present work a PET hexamer of monohydroxyethyl terephthalate 2-HE-(MHET) 6 , was used to search for potential additional binding pockets for the ligand. The analysis of the docked poses of the PET hexamer 2-HE-(MHET) 6 shows that the terminal monomers (which interact with regions of the proteins located before and after the subsite I and IIc, respectively) display a high flexibility, while the conformation of the four central monomers (which bind the enzyme in the subsites I, IIa, IIb, and IIc) is similar to the one reported in previous studies [ 16 , 18 , 19 , 20 ] in which the tetramer 2-HE-(MHET) 4 was used as the ligand. The ligand-enzyme complex was analyzed by MD simulation ( Figure 2 A and Figure S1 ) to assess the stability of such interactions.…”
Section: Resultssupporting
confidence: 78%
“…As a result, the dependability of the screening protocol we presented is validated. Despite the fact that molecular docking and MD simulations revealed positions 57–64 (the β1–β2 connecting loop (L3), Figure 1 ) to be flexible and thus suitable for mutagenesis, no experimental results were reported [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to difficulties in co-crystallization and the low solubility of the PET polymer, the PETase structure in complex with PET is still unavailable [ 23 , 25 ]. As a result, only computational approaches, such as molecular docking and molecular dynamics (MD) (i.e., quantum mechanics/molecular mechanics (QM/MM) and a density functional theory (DFT)-based QM/MM) have been employed to investigate their binding mode and molecular interactions [ 22 , 23 , 26 , 28 , 29 , 30 ]. Although the proposed PETase catalytic mechanisms from these studies are similar in that PET depolymerization occurs at the active site of PETase (S160, H237, and A206) with the help of other hydrophobic residues around the binding cleft that brings the carbonyl carbon atom of PET into close contact for nucleophilic attack from S160, the reaction mechanism of Ser–His–Asp-initiated nucleophilic attack is still inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…30 A lot of efforts have been made on IsPETase/IsMHETasecatalyzed processes. 14,[29][30][31]41,43 Recently, Boneta et al compared the depolymerization mechanism of PET catalyzed by IsPETase and leaf-branch compost cutinase (LCC-ICCG) with theoretical approaches, where they showed that the depolymerization mechanism of two enzymes is similar. 40 Here, with the high level (DFT) quantum mechanics/ molecular mechanics method (QM/MM), the detailed cascade degradation process of IsPETase and IsMHETase was fully explored in a step-by-step manner.…”
Section: ■ Introductionmentioning
confidence: 99%